A combined low‐ and high‐cycle life prediction model considering the closure effect of micro‐defects. Issue 7 (25th April 2022) - Ding, Xin; Yan, Xiaojun; Guo, Zixu; Guo, Kaimin
Abstract: In this study, a combined low‐ and high‐cycle fatigue (CCF) life prediction model, which considers the crack closure effect (CCE) of micro‐defects, is proposed based on the continuous damage mechanics. The model is decomposed into three submodels: the low‐cycle fatigue (LCF), high‐cycle fatigue (HCF) under the maximum stress of LCF (HCFML), and their coupled damage models. The experimental CCF data of K403 full‐scale turbine blades are used to verify the accuracy. The prediction life falls within the ±2.62 times of scatter band compared with the experimental results. Further, there are the different damage evolution forms at different vibration stresses. When the vibration stress is below 29 MPa, the CCF damage mainly is caused by the LCF. However, while the vibration stress is above 29 MPa, the HCFML damage plays a major role. The CCF damage of the first stage serration of K403 turbine blades is mainly from HCFML. Highlights: New combined low‐ and high‐cycle fatigue (CCF) life prediction model. Consider the crack closure effect of micro‐defects based on the damage mechanics. Evolution laws of damage rate and damage under CCF loads. The main damage to the serrations of turbine blades in the actual external field.